A prospective study of BurstDR™ spinal cord stimulation for non‐operated discogenic low back pain. Issue 3 (23rd November 2022) - Mons, Martijn R.; Chapman, Kenneth B.; Terwiel, Chris; Joosten, Elbert A.; Kallewaard, Jan‐Willem
Abstract: Introduction: Chronic discogenic low back pain (CD‐LBP) is caused by degeneration of the disc due to trauma to the annulus or by unprovoked degeneration, resulting in chronic pain. Spinal cord stimulation (SCS) employing the BurstDR™ waveform has been shown to be an effective treatment in a variety of chronic pain conditions. The aim of this prospective case study was to determine the effect of BurstDR™ SCS on pain relief, disability, and patient satisfaction in a population with CD‐LBP. Methods: Seventeen subjects with CD‐LBP received a SCS trial with BurstDR™ stimulation. Patients with >50% pain relief after a trial period of 2 weeks were permanently implanted ( n  = 15). Patients then rated LBP and leg pain using the numeric rating scale (NRS), Oswestry disability index (ODI), patient global impression of change (PGIC), EQ‐5D quality of life, and painDETECT for neuropathic pain at baseline following trial, 3, 6, and 12 months after permanent implantation. Results: Treatment with BurstDR™ SCS resulted in significant reduction of LBP as the NRS was reduced from 71.7 ± 7.3 at baseline to 42.5 ± 18.1 at 12 months. Average pain relief at 12 months was 42.5%. In patients with leg pain ( n  = 8), pain was significantly reduced from 66.9 ± 8.2 to 11.7 ± 10.4 at 12 months. PainDETECT scores for neuropathic pain significantly reduced from 18.9 ± 4.8 at baseline, and 14.8 ± 3.2 at 12 months. Baseline ODI score significantly reduced from 41.2 ± 12.8 to 25.8 ± 8.6 at 12 months. PGIC scores remained low from 2.6 ± 1.6 at 3 months, 2.5 ± 1.0 at 6 months, and 2.5 ± 1.3 at 12 months. EQ‐5D‐5L rates remained constant from baseline 56.10 ± 23.9 to 68.6 ± 12.9 at 12 months. Conclusion: BurstDR™ SCS resulted in significant reduction of back pain, leg pain, and quality of life in patients with CD‐LBP and decreased the level of disability and generated positive patient satisfaction scores.